Minimal residual disease assessment following CD19-targeted therapy in B-cell precursor acute lymphoblastic leukemia using standardized 12-color flow cytometry: A EuroFlow study - Verbeek, Martijn W C; Reiterová, Michaela; Laqua, Anna; Rodríguez, Beatriz Soriano; Sedek, Lukasz; Buracchi, Chiara; Buysse, Malicorne; Oliveira, Elen; Engelmann, Robby; Desterro, Joana; De Jong, Anja X; Boettcher, Sebastian; et al. (HemaSphere, 2025)
Detection of minimal/measurable residual disease (MRD) is a critical prognostic marker in B-cell precursor acute lymphoblastic leukemia (BCP-ALL). The EuroFlow Consortium previously developed an 8-color flow cytometric MRD protocol, effective for >98% of BCP-ALL patients treated with chemotherapy. This study aimed to enhance MRD detection, particularly for patients treated with CD19-targeted therapies, by expanding the EuroFlow protocol to a 12-color panel. This new panel incorporates additional B-cell markers and exclusion T/NK-cell markers (CD3 and CD7). Through an evaluation of 237 diagnostic BCP-ALL samples, CD22, CD24, and HLA-DR were selected as additional B-cell gating markers. Two 12-color tubes were technically optimized and clinically validated across 101 patient follow-up samples, demonstrating excellent concordance with molecular MRD levels (R 2 = 0.88). The 12-color BCP-ALL MRD tubes were compatible with the previously developed 8-color automated gating and identification (AGI) tool and demonstrated good reproducibility. Our findings indicate that the 12-color panel performs comparably to the 8-color BCP-ALL MRD panel, including both CD19-positive and CD19-negative cases. However, it offers an improved definition of the B-cell lineage, particularly for expert-guided manual data analysis, and provides additional information on the expression of the targetable marker CD22.